Appropriateness of Cotrimoxazole Prophylactic Therapy Among HIV/AIDS Patients in Public Hospitals in Eastern Ethiopia: A Retrospective Evaluation of Clinical Practice - Sisay, Mekonnen; Bute, Dida; Edessa, Dumessa; Mengistu, Getnet; Amare, Firehiwot; Gashaw, Tigist; Bihonegn, Temesgen (Frontiers in Pharmacology, 2018)
Background: Cotrimoxazole prophylactic therapy (CPT) is a feasible, cost-effective, and safe way of using cotrimoxazole intervention to reduce HIV/AIDS related morbidities and mortalities associated with opportunistic infections. Despite its effectiveness in reducing the incidence of opportunistic infections, the actual drug utilization process has been shown to deviate from World Health Organization (WHO) guideline in Ethiopia. This study, therefore, aims to evaluate CPT among HIV/AIDS patients in Jugel Hospital (JH), Harar and Dilchora Referral Hospital (DRH), Dire Dawa, Eastern Ethiopia. Methods: A cross sectional study was conducted to evaluate the use of cotrimoxazole as prophylactic therapy. In this study, 556 medical records (305 in JH and 251 in DRH) of HIV/AIDS patients who had been taking CPT within September 2015–August 2016 were reviewed. Systematic random sampling was employed to obtain medical records from the sampling frame. Data were abstracted from the patient medical records using structured checklist customized from the WHO guideline. The data were entered into Epi-data 3.1 and exported to and analyzed with statistical Package for Social Sciences (SPSS) version 20. The finding was evaluated against the WHO guideline on the use of cotrimoxazole prophylaxis in HIV/AIDS patients. Descriptive statistics was used to present the data in tables, figures and pie chart. Results: Majority of the HIV/AIDS patients who had been taking CPT were adults (95.9%), female (61.2%), married (43.7%), Orthodox Christian (54.3%), and attended primary school (40.1%). At the initiation of CPT, most of the patients were at WHO clinical stage III (40.8%). The major comorbid illnesses identified were tuberculosis and pneumocystis-jiroveci pneumonia. Initially, majority of the patients were at CD4 count of less than 350 cells/mm3 (n = 504, 90.6%). Greater proportion of patients started CPT prior to initiating antiretroviral therapy (ART). Most of the patients took CPT for greater than 6 months. The primary reasons for premature discontinuation of CPT were CD4 greater than 350 cells/mm3, severe sulfa allergy and first trimester of pregnancy. Generally, the use of cotrimoxazole prophylaxis was consistent with the WHO guideline for indication to start (n = 519, 93.3%) and dose (n = 552, 99.28%), despite the presence of contraindication in 6.65% patients. Conclusion: In reference to the WHO guideline, the use of CPT was found to be fully appropriate in nearly two-thirds of HIV/AIDS patients. For the rest patients, inappropriate use of cotrimoxazole was observed based on the WHO criteria for initiation, discontinuation, continuation and dose with rate of discontinuation being the dominant one. Such practice may lead to adverse health outcomes including adverse drug reactions and negative treatment outcome.